On the development of a technical specification for the use of fine recycled aggregates from construction and demolition waste in concrete production - Bravo, Miguel (2020)
The possibility of using recycled aggregates from construction and demolition waste (CDW) in concrete is rather widely agreed upon when it comes to the use of coarse recycled aggregates. However, this is not the case when fine recycled aggregates (FRA) are considered, as it is deemed that these seriously impair the behaviour of concrete. Hence, this work presents a technical specification proposal for the use of FRA from CDW in concrete, to attempt to fill this gap in legislation. The specification is based on a wide collection of experimental results, from which it is shown that for low incorporation ratios (up to 25%), the properties of concrete with FRA from CDW are comparable to those of a reference concrete. The intended international scope of the specification is ensured by the fact that FRA from CDW are typified by composition (percentage of concrete, masonry, glass, etc.) rather than by geographical origin or construction type. It is shown that, after typifying the FRA and assuming, as per design, the acceptable percentage losses (relative to a reference concrete) of mechanical, durability-related and long-term physical properties, if the maximum incorporation ratios proposed of each type of FRA are used, the variation of properties remains within the limits established.